Acrylamide Content of Experimental Flatbreads Prepared from Potato, Quinoa, and Wheat Flours with Added Fruit and Vegetable Peels and Mushroom Powders - Lauren M. Crawford; Talwinder S. Kahlon; Selina C. Wang; Mendel Friedman (Foods, 2019)
Flatbreads are a major food consumed worldwide. To mitigate an undesirable safety aspect of flatbreads that might be associated with the potentially-toxic compound acrylamide, we recently developed recipes using a variety of grains that resulted in the production of low-acrylamide flatbreads. To further enhance the functionality of flatbreads, we have developed, in this work, new experimental flatbreads using potato, quinoa, and wheat flours supplemented with peel powders prepared from commercial nonorganic and organic fruits and vegetables (apples, cherry tomatoes, melons, oranges, pepino melons, sweet potato yams), potato peels, and mushroom powders (Lion’s Mane, Hericium erinaceus; Reishi, Ganoderma lucidum; and Turkey Tail, Trametes versicolor). These additives have all been reported to contain beneficial compositional and health properties. The results of fortification of the baked flatbreads showed either no effect or increases in acrylamide content by unknown mechanisms. Since the additives did not increase the acrylamide content of the quinoa flour flatbreads for the most part, such supplemented quinoa flatbreads have the potential to serve as a nutritional, gluten-free, low-acrylamide, health-promoting functional food. Mushroom powder-fortified wheat flatbreads with relatively low acrylamide content may also have health benefits.